Environmental driver effects on population growth rates vary by rarity type and variation in demographic rate sensitivity - Herzog-Ramirez, Sarah (My University, 2024)
Abiotic and biotic drivers, such as climate or herbivores, influence populations; however, their effects could vary by population or rarity type (range size, habitat specificity, and population density). I examined how the effects of drivers on vital rates could impact population growth due to variation of population growth sensitivity to demographic rates. I found significant variation in effects of neighbors on population growth rate, which is driven primarily by variation in sensitivity to demographic rates across populations. Further, results from a climate warming experiment suggests variation in life history across populations is partly driven by temperature differences. In a separate study, I test the niche breadth hypothesis, which postulates that driver effect sizes should decrease with range size. I estimated the effects of abiotic (climate and fire) and biotic (insect and mammal herbivory) drivers across nearly one hundred tallgrass prairie plant species of varying range size. I found biotic driver effects increase with range size, counter to the niche breadth hypothesis but in accordance with other recent work. Additionally, I model population growth rate for 15 tallgrass prairie species varying in rarity type to examine how the impacts of drivers vary across rarity types, and how these drivers, in combination with dispersal ability, might impact climate change induced range shifts. I found effects of climate, fire, and grazing have minimal effects on population growth rate for all species. However, I found strong deviations in dispersal for species varying in habitat specificity and dispersal ability. In total, our results emphasize effects of drivers can vary across populations and across rarity types. Without taking these differences into this consideration, management and conservation practices could have unanticipated effects.
Keywords: Ecology; Grasslands; Population; Rarity; Plants